Beyond the Rhetoric: Maternal, Newborn and Child Survival in Nepal - Sharma, G; Pandey, S (Nepal Journal of Obstetrics and Gynaecology, 2016)
Nepal has performed exceptionally in improving reproductive, maternal and child health outcomes over the past two decades. In this article, we discuss these achievements and outline a vision for the future of maternal, newborn and child survival in Nepal after the era of the Millennium Development Goals. On the pathway towards quality universal health care services for all, we propose strengthening of health information systems, gradual health system reforms, improvement of existing facility based services, development of integrated service delivery models, improved technical and managerial capacity at district and facility levels. Elimination of all preventable causes of maternal, newborn and child deaths in Nepal should be our collective aspirational goal.